Dampak Terhadap Masyarakat Kampung Sentul Dengan Adanya Industri Alkohol Melalui Pendekatan Teori AGIL - Bayu Aji Hakiki; Argyo Demartoto (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
The industrialization of ethanol alcohol at the local community level creates a dilemma between economic growth and complex social-environmental externalities. This research analyzes the multidimensional impacts of the alcohol industry on social, environmental, and economic conditions in Kampung Sentul, Bekonang Village, Mojolaban District, Sukoharjo Regency. The research objectives are to identify community adaptation mechanisms, inter-stakeholder interest conflicts, environmental degradation from production waste, and local economic structural transformation. A qualitative method with case study design was implemented through in-depth interviews with 15 informants (craftsmen, workers, community leaders, village officials, environmental activists), participatory observation, and documentation analysis during June 2024-January 2025. Data analysis utilized the Miles-Huberman interactive model with Talcott Parsons' structural functionalism theoretical framework (AGIL). The research gap lies in the scarcity of studies holistically integrating social-environmental-economic impacts within the context of informal alcohol industries in Indonesia. The research novelty is the application of AGIL theory to understand social system equilibrium dynamics amid economic transformation based on controversial industries. Findings indicate that the alcohol industry creates structural tension between economic adaptation functions and dysfunctions in social integration and cultural value maintenance, necessitating policies balancing economic growth with social-environmental protection.